Post-splenectomy accessory spleen hyperfunction in children with hereditary spherocytosis: a rare case report and literature review - He, Yuan-fei; Qi, Shi-qin; Bian, Jian; Zhou, Cheng-xiao; Zhang, Pei (Frontiers in Pediatrics, 2025)
ObjectiveTo enhance the understanding of splenectomy in children with hereditary spherocytosis, specifically focusing on the preservation of accessory spleens or partial splenectomy.MethodsA retrospective review of clinical data and surgical methods of a child with hereditary spherocytosis who underwent surgery for accessory spleen hyperfunction 7 years after splenectomy at the General Surgery Department of Anhui Provincial Children's Hospital, along with a literature review.ResultsThe child successfully underwent single-port plus one laparoscopic accessory spleenectomy. The surgery lasted 195 min, with an estimated blood loss of 600 ml. The postoperative hospital stay was 8 days, and at 6 months of follow-up, there were no complications such as bleeding, wound infection, thrombosis, or adhesive intestinal obstruction.ConclusionFor children with hereditary spherocytosis, the decision to preserve the spleen or accessory spleens during surgical treatment offers important reference value.